High-Tech Versus High-Touch: Components of Hospital Costs Vary Widely. Issue 3 (May 2017) - Song, Paula H.; Reiter, Kristin L.; Yi Xu, Wendy
Abstract : EXECUTIVE SUMMARY: The recent release by the Centers for Medicare & Medicaid Services of hospital charge and payment data to the public has renewed a national dialogue on hospital costs and prices. However, to better understand the driving force of hospital pricing and to develop strategies for controlling expenditures, it is important to understand the underlying costs of providing hospital services. We use Medicare Provider and Analysis Review inpatient claims data and Medicare cost report data for fiscal years 2008 and 2012 to examine variations in the contribution of "high-tech" resources (i.e., technology/medical device-intensive resources) versus "high-touch" resources (i.e., labor-intensive resources) to the total costs of providing two common services, as well as assess how these costs have changed over time. We found that high-tech inputs accounted for a greater proportion of the total costs of surgical service, whereas medical service costs were primarily attributable to high-touch inputs. Although the total costs of services did not change significantly over time, the distribution of high-tech, high-touch, and other costs for each service varied considerably across hospitals. Understanding resource inputs and the varying contribution of these inputs by clinical condition is an important first step in developing effective cost control strategies.